ANALYSIS OF WORK RISK LEVEL WITH SUITABILITY OF SAFETY SIGN AT PT. AIR MANCUR KARANGANYAR - Pipid Ari Wibowo; Avicena Sakufa Marsanti; Alfiatul ‘Ula (International Journal of Health Literacy and Science, 2023)
Production activities that use machines pose a risk of danger to workers. The maintenance and repair of machines in the production process also has many potential hazards. So the purpose of this study was to analyze the effect of the level of occupational risk on the suitability of the safety sign at PT. Air Mancur Karanganyar. Hazard Identification Risk Assessment Determinant Control (HIRADC) method is a way of identifying hazards, risks and determining control of hazards. This study used a cross sectional quantitative, the sampling technique used was Porportionate Statified Random Sampling is if the population had members or elements that had proportional strata with the samples being 38 people. The inclusion criteria for this study were workers in engineering rooms, Solid External Medicines (OLP), and cosmetics at PT. Air Mancur Karanganyar. Data analysis of a spearmen correlation test. The results that there is a significant influence between the Level of Occupational Risk on the Compliance of the Safety Sign at PT. Air Mancur Karanganyar with a significance value of 0.012. The recommendations is are the placement of safety signs such as the Caution for Pinched Hands sign, routine socialization twice a week, and review HIRADC once a year